Perancangan Cat – Friendly Furniture pada Rumah Tinggal - Anita Alexandra (Intra, 2017)
Cat – friendly furniture is a furniture that can accommodate human and their cat daily needs. The design of this furniture based on needs and activity of human and cat while inside the home. Residential Home was selected for design because human and cat spend  many time together there. Beside that, cat likes to spend a lot of its time at home more than playing outside. The design method used is Design Thinking that collect, observe, and analysis facts about user’s needs and activity as foundation when  designing Cat – friendly furniture .The design of this furniture using geometric and arc shape so it will  be safe when used by human and cat. Materials and finishing that used for this furniture is safe for the users. Some part of this furniture can be plug out and plug in so users can easily change that parts.  Cat – friendly furniture can be used for a long time even when the users not having a cat anymore, so the it won’t be negelected.